Near-Field Thermometry Sensor Based on the Thermal Resonance of a Microcantilever in Aqueous Medium - Kim, Seonghwan (Molecular Diversity Preservation International (MDPI), 2007)
A new concept using a near-field thermometry sensor is presented, employing a tipless microcantilever experimentally validated for an aqueous medium within approximately one cantilever width from the solid interface. By correlating the thermal Brownian vibrating motion of the microcantilever with the surrounding liquid temperature, the near-field microscale temperature distributions at the probing site are determined at separation distances of z = 5, 10, 20, and 40 μm while the microheater temperature is maintained at 50(°)C, 70(°)C, or 90(°)C. In addition, the near-field correction of the correlation is discussed to account for the quenched cantilever vibration frequencies, which are quenched due to the no-slip solid-wall interference. Higher thermal sensitivity and spatial resolution is expected when the vibration frequencies increase with a relatively short and thick cantilever and the dimensions of the microcantilever are reduced. Use of the microcantilever thermometry sensor can also reduce the complexity and mitigate the high cost associated with existing microfabricated thermocouples or thermoresistive sensors.